Pengaruh Pengungkapan Sustainability Report dan Nilai Aset Tidak Berwujud Terhadap Kinerja Keuangan Perusahaan (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2018-2021) - Gregorius Fico Faransahad; Ika Wulandari (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This study aims to evaluate the impact of sustainability report disclosure including the performance aspects in it (economic, environmental, social) and the value of intangible assets on financial performance projected by return on assets in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018-2021. This research is a casual comparative research that utilizes quantitative measures. The data collection method applied is documentation. Information to be researched through the IDX website as well as individual websites of the companies that are the research sample. Data analysis was carried out using descriptive statistical techniques, classical assumption tests, and hypothesis testing. The findings of this study indicate that the disclosure of economic performance has a positive impact on the company's financial performance, while the disclosure of environmental performance and social performance also has a positive impact on the company's financial performance. In addition, the disclosure of intangible asset values also has a significant positive impact on the company's financial performance.